2017
DOI: 10.1093/treephys/tpx140
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of branch and leaf hydraulics in adult Fagus sylvatica and Picea abies in a forest through-fall exclusion experiment

Abstract: Decreasing water availability due to climate change poses the question of whether and to what extent tree species are able to hydraulically acclimate and how hydraulic traits of stems and leaves are coordinated under drought. In a through-fall exclusion experiment, hydraulic acclimation was analyzed in a mixed forest stand of Fagus sylvatica L. and Picea abies (L.) Karst. In drought-stressed (TE, through-fall exclusion over 2 years) and control (CO) trees, hydraulic vulnerability was studied in branches as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 76 publications
1
39
0
Order By: Relevance
“…These values are in good agreement with those reported in other studies on beech saplings (Caquet et al () and Aranda et al () reported values of −3.0 to −4.0, and −3.0 to −3.7 MPa, respectively), while there are also studies that found less negative values (Cochard et al () and Barigah et al ) reported values of −2.5 to 3 and −2.5 MPa, respectively). Studies on mature beech trees also resulted in similar values (Lemoine et al , , −2.2 to −3.1 MPa; Herbette et al , , −3.0 MPa; Schuldt et al , , −3.3 to −3.7 MPa; Stojnic et al , , −2.9 to −3.5 MPa; Tomasella et al , , −2.5 MPa). In the framework of the current study we have not been able to cross‐correlate our results with established benchmark methods.…”
Section: Discussionmentioning
confidence: 76%
“…These values are in good agreement with those reported in other studies on beech saplings (Caquet et al () and Aranda et al () reported values of −3.0 to −4.0, and −3.0 to −3.7 MPa, respectively), while there are also studies that found less negative values (Cochard et al () and Barigah et al ) reported values of −2.5 to 3 and −2.5 MPa, respectively). Studies on mature beech trees also resulted in similar values (Lemoine et al , , −2.2 to −3.1 MPa; Herbette et al , , −3.0 MPa; Schuldt et al , , −3.3 to −3.7 MPa; Stojnic et al , , −2.9 to −3.5 MPa; Tomasella et al , , −2.5 MPa). In the framework of the current study we have not been able to cross‐correlate our results with established benchmark methods.…”
Section: Discussionmentioning
confidence: 76%
“…Enhanced compensation growth of fine roots upon drought (e.g., in beech, Meier and Leuschner et al 2008), adjustment of the mycorrhiza to an increased share of longdistance exploration types (Nickel et al 2018), and acclimation of the branches and leaves to drought (Barbeta and Penuelas, 2016;Tomasella et al 2018) may be effective measures of drought acclimation.…”
Section: Discussionmentioning
confidence: 99%
“…and European beech (Fagus sylvatica [L.]) to natural episodic and experimentally extended drought in mature monospecific and mixed-species stands of Norway spruce and European beech in the Kranzberg Forest. This study utilized the throughfall exclusion experiment KROOF in the Kranzberg Forest (Pretzsch et al 2014;Tomasella et al 2018;Hesse et al 2019) and additional long-term tree measurements nearby (Pretzsch et al 1998). To better understand the long-term effects of drought on tree growth in intra-and inter-specific environments, we concentrated on the following questions and hypotheses: Q1: How do species react to natural drought events (represented by the years 2003 and 2015) in intra-versus interspecific environments?…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown plastic responses (variations in phenotype expression in response to environmental change) of leaf physiology and plant architecture to experimental or natural drought (Ambrose, Sillett, & Dawson, ; Dayer et al, ; Egea et al, ; Prendin, Mayr, Beikircher, von Arx, & Petit, ; Yue et al, ). Some studies also report plastic responses in hydraulic traits to short‐term drought, related to both hydraulic safety and hydraulic efficiency (Awad, Barigah, Badel, Cochard, & Herbette, ; Beikircher & Mayr, ; Prendin et al, ; Tomasella et al, ). However, whether this plasticity can positively influence plant function (e.g.…”
Section: Introductionmentioning
confidence: 99%